THE PERFORMANCE OF INDONESIAN ISLAMIC RURAL BANKS DURING COVID-19 OUTBREAK: THE ROLE OF DIVERSIFICATION - Risfandy, Tastaftiyan; Pratiwi, Desti Indah (Journal of Islamic Monetary Economics and Finance, 2022)
This research investigates how Islamic rural banks performed during the Covid-19 outbreak and how diversification is associated with the performance of the banks. Islamic rural banks provide a unique setting because they serve limited customers in a specific region in Indonesia, different from national commercial banks that accommodate all types of customers in all regions. To investigate this issue, we employ panel data of 164 Islamic rural banks dispersed across 23 provinces in Indonesia from 2020q4-2021q3. We find that covid-19 is negatively associated with the profitability of Islamic rural banks, implying that covid 19 has affected all sectors, including banks with niche markets such as Islamic rural banks. We also find that diversification is negatively related to the Islamic rural banks’ performance. This finding suggests that instead of expanding their business scope, Islamic rural banks should focus on their main business activity because their non-financing income is adversely related to their performance. Our finding suggests that policymakers effectively monitor Islamic rural banks to remain focused on their main business activity.